Mompreneurs: Standing Up With Life Choices, Family Support, Patriarchal Culture in Madura, and The Covid-19 Pandemic - Yuni Rimawati; Habi Bullah; Adi Darmawan Ervanto (School of Business, IPB University (SB-IPB), 2022)
This study aims to explore the learning experience of mompreneurs who have studied in college with patriarchal culture setting in Madura in combating the crisis caused by the covid-19 pandemic. This study used a case study methodology with a multi-case approach. Data were obtained through observations, interviews, and digital tracing. This study reveals that based on all the cases, being mompreneurs and not working in the formal sector is a choice to focus on running the duty as a mother and on getting full support from husband and family. In running the business and family, there is collective consciousness that all the revenue received by family members are blessings (rejeki) from Allah by getting it through halalan tayyiban principle. The promotions have used social media with various intensities. The Covid-19 Pandemic significantly affects mompreneurs whose primary basis is in-person selling, while online selling was not affected. The experimental learning during the Covid-19 Pandemic is maximizing promotions through social media, cutting operational costs, changing the payroll system to profit sharing, and broadening the business lines. Keywords: mompreneurs, the patriarchal, family support, the covid-19 pandemic, learning experience